Serbia and the European Union: A Decade of Negotiating Challenges (2014–2024) - Styczyńska, Natasza (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
The article analyses Serbia’s EU accession negotiations (2014–2024), focusing on the interplay between domestic politics and foreign policy objectives. Serbia’s pragmatic foreign policy balances EU aspirations with strategic partnerships (Russia, China, US), reflecting its historical context (NonAligned Movement) and the Kosovo issue. Employing a qualitative methodology, including a literature review and 2024 interviews with Serbian political actors (politicians, experts, and public servants) this article discusses challenges in the EU negotiations and the insignificant progress, pointing out the unresolved Kosovo issue as one of the major political obstacles. Despite the Serbian government’s stated priorities, the analysis suggests a disconnect between the rhetoric and actions of both the EU and Serbian political elite. The EU’s commitment to the region is evident (e.g., Western Balkans Growth Plan), but Serbia’s internal challenges and ambivalent stance significantly diminish the likelihood of swift EU accession. This article offers insights into the complexities of Serbia’s EU integration seen from the perspective of domestic political actors. Artykuł analizuje negocjacje akcesyjne Serbii z UE (2014–2024), koncentrując się na wzajemnym oddziaływaniu polityki wewnętrznej i celów polityki zagranicznej. Pragmatyczna polityka zagraniczna Serbii równoważy aspiracje UE ze strategicznymi partnerstwami (Rosja, Chiny, USA), odzwierciedlając jej kontekst historyczny (Ruch Państw Niezaangażowanych) i kwestię Kosowa. Wykorzystując metodologię jakościową, w tym przegląd literatury i wywiady z serbskimi aktorami politycznymi (politykami, ekspertami i urzędnikami państwowymi), niniejszy artykuł omawia wyzwania w negocjacjach z UE i nieznaczne postępy, wskazując na nierozwiązaną kwestię Kosowa jako jedną z głównych przeszkód politycznych. Pomimo deklarowanych przez serbski rząd priorytetów, analiza sugeruje rozdźwięk między retoryką a działaniami zarówno UE, jak i serbskich elit politycznych. Zaangażowanie UE w regionie jest oczywiste (np. Plan Wzrostu Bałkanów Zachodnich), ale wewnętrzna polityka Serbii i jej ambiwalentne stanowisko znacznie zmniejszają prawdopodobieństwo szybkiego przystąpienia do UE. Niniejszy artykuł oferuje wgląd w złożoność integracji Serbii z UE z perspektywy krajowych aktorów politycznych.
Negocjacje Serbii z Unią Europejską: Dekada Wyzwań (2014–2024)
Keywords: Serbia; European Union; EU Enlargement; Western Balkans; Foreign Policy; Unia Europejska; rozszerzenie UE; Bałkany Zachodnie; polityka zagraniczna